Pembinaan Kemandirian Mebel bagi Narapidana dalam Mewujudkan Tujuan Sistem Pemasyarakatan - Equatora, Muhammad Ali; Butar Butar, Herry Fernandes (Sosio e-Kons, 2024)
Indonesia Pemasyarakatan System is the answer of global dynamism regarding treatment of law offender inside Correctional Institutions. Pemasyarakatan System replaced Imprisonment System that more retributive and fail to fulfil human rights value. Pemasyarakatan system is giving an opportunity to every law offender to become obedient citizen with its own personality guidance that focusing on character development and craftmanship guidance that focusing on skills development. This research intends to describe the process of craftmanship guidance that held by Lembaga Pemasyarakatan Kelas IIB Siborongborong as its effort to achieve Pemasyarakatan System goal. This research used qualitative method which the researcher found primary data from official sources and official document. Researcher successfully found how the process of craftmanship guidance and the efforts from external and internal instructor. The guidance process was the form of Pemasyarakatan System Goals.